Attitudes of Teachers Toward the Developed Social Studies Curriculum (the Basic Fourth Grade as a Model) Field study in the schools of Lattakia - Jnad, Rawha; Sultan, Manal; Jahjah, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study aimed at recognizing the attitudes of teachers toward the development social studies curriculum of the basic fourth grade of the school year(2018\2019) according to the variables of the (qualification, experience and training) in Lattakia. The descriptive analytical method was used. Where the researcher has prepared the attitude scale which consists of(28) statement, then it was applied randomly on a sample consists of(96) classroom instructors, who have tought the curriculum of development social studies at the basic fourth grade. The study has the results, that the attitudes of teachers toward the developed curriculum were negative ingeneral, where the total means was(1.98), in addition, The study came to results that there were statistical significant differences at the level of(0.05) between the means scores of teachers attitudes on the attitude scale according to the variable of qualification in the favor of the high qualification, and according to the variable of experience in the favor of teachers who have less than five years experience, while there weren't any statistical significant differences according to the variable of attending training sessions. The results led the researcher to recommend of the continuous necessity of the importance of the social studies curriculum at the first cycle of the basic learning, and to activate the communication with teachers concerning the developed curricula, and to produce much importance for training, and concentrating on its quality.